2022
DOI: 10.1002/fuce.202100057
|View full text |Cite
|
Sign up to set email alerts
|

Experimental investigation of stable the proton exchange membrane fuel cell control using magnetic sensor probes

Abstract: In proton exchange membrane fuel cells (PEMFCs), the avoidance and detection of failures such as flooding and dry-out are crucial. Non-destructive measurement approaches using magnetic sensors have been developed for this purpose.To reduce the number of sensors required to be installed in a PEMFC system for evaluation, we propose a control method for PEMFCs using the magnetic flux density as an index. The proposed method determines the failure conditions by calculating a simple current mapping with a reduced n… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 38 publications
0
3
0
Order By: Relevance
“…Mapping modifications of such magnetic fields can be employed as non-invasive diagnosis methods to detect and isolate faults in PEMFC themselves. Changes in current density distribution inside PEM and overall performances can be monitored using magneto-tomography data [ 429 , 430 , 431 , 432 , 433 , 434 , 435 , 436 ]. Some authors also investigated the effect of these self-induced magnetic fields on the corrosion of the metal bipolar plates in PEMFCs.…”
Section: Basics Of Fuel Cellsmentioning
confidence: 99%
“…Mapping modifications of such magnetic fields can be employed as non-invasive diagnosis methods to detect and isolate faults in PEMFC themselves. Changes in current density distribution inside PEM and overall performances can be monitored using magneto-tomography data [ 429 , 430 , 431 , 432 , 433 , 434 , 435 , 436 ]. Some authors also investigated the effect of these self-induced magnetic fields on the corrosion of the metal bipolar plates in PEMFCs.…”
Section: Basics Of Fuel Cellsmentioning
confidence: 99%
“…Based on the experimental data in [4], a method to calculate the current intensity distribution the magnetic field at four points is presented in this study. The experiment was performed using a 5-cell PEMFC stack with a constant current of 15 A for 1 h and an unhumidified hydrogen and air supply.…”
Section: Pemfc System and Conditionsmentioning
confidence: 99%
“…According to our research, the number of measurement points can be reduced and evaluated by inserting them in an air-cooled fuel cell [3]. We have also previously demonstrated that the system can be used for control as it enables real-time identification of faults such as flooding or dry-out by considering the measurements from at least two magnetic sensors, but only the current distribution at the time of the fault [4].…”
Section: Introductionmentioning
confidence: 96%